MENINGKATAN ETOS KERJA BERBASIS RELIGIUSITAS PEKERJA PABRIK DI KAWASAN INDUSTRI (STUDI KASUS DI LPKS MYNARA CIKARANG) - Muhammad Hasyim; Siti Uswatun Hasanah; Muh Asy’ari Akbar (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2024)
ABSTRACK This research aims to gain a deep understanding of the role of religiosity in shaping the work ethic of factory workers in LPKS Mynara Cikarang. In this research approach, a qualitative method was employed, focusing on data collection through in-depth interviews and participatory observation. The research respondents consisted of factory workers at LPKS Mynara Cikarang with diverse work experiences. The findings of this research depict religiosity not only as a series of religious rituals but also as a profound awareness that permeates moral values and personal engagement with God. These religious values provide a strong moral foundation, creating a work culture based on a moral calling rather than tasks as mere obligations. Religious practices, such as prayer and self-reflection, are not just rituals but also psychological strategies that positively impact the psychological well-being of workers. The research also highlights the challenges and opportunities in enhancing the work ethic of factory workers. Training and skills development are recognized as strategic pillars, while leadership roles that set positive examples and engage in open communication are identified as keys to motivating workers. However, high levels of stress and workload can hinder productivity, indicating the need for management policies that support employee well-being. Adaptation to technological changes is also crucial, requiring relevant training and effective communication. Overall, these findings provide a foundation for companies to develop holistic strategies that incorporate training, leadership, stress management, and technological adaptation to sustainably enhance the work ethic of factory workers.